Propostas de atividades para o ensino de geometria baseadas em construções geométricas com origami - CAVALCANTE, Wilnaianny Lidel Pedroso (Universidade Federal do Oeste do Pará, 2022)
The objective of this research was to propose activities for the teaching of Mathematics, more precisely for the teaching of Geometry, through geometric constructions with origami. The proposed activities of this dissertation are presented as relevant alternatives for teaching practice, since they make use of paper manipulation, which is very accessible due to its low cost. A bibliographical research was used in this study. The main result was the production of a set of four activities that could be used in math classes to teach geometry in the 9th grade of elementary school. They address some essential geometric contents that must be worked on in the final years of Elementary School according to the Common National Curricular Base. We believe that the activities and the text produced in this dissertation can be interesting and instructive for both those who teach and those who learn.